VALIDATION OF IN-SERVICE TEACHER ORIENTATION PROGRAMME (INSTOP) AS A MODEL FOR IN-SERVICE TRAINING OF TEACHERS IN PAKISTAN - Muhammad Tayyab Alam Bukhari, Arifa Awais (PJE, 2023)
This study was designed to validate the INSTOP model which had been developed by the researcher himself in 2001 on the basis of the data collected from 240 in-service teacher trainers in Pakistan. For this purpose, a questionnaire was developed.